2003
DOI: 10.1001/archotol.129.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prior Hyperbaric Oxygen Therapy in Complications Following Microvascular Reconstruction for Advanced Osteoradionecrosis

Abstract: Microvascular reconstruction is effective in the treatment of patients with mandibular ORN. Management of mandibular ORN can be successfully achieved without the use of perioperative HBO therapy. Because only 3 patients received perioperative HBO therapy, we are unable to comment on its potential benefit. Patients in whom prior HBO therapy has failed are significantly more likely to have surgical complications than are other patients with Marx stage III disease, and further study is required to improve outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
58
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(63 citation statements)
references
References 7 publications
2
58
0
3
Order By: Relevance
“…[20][21][22] Our group and others, however, have demonstrated that hyperbaric oxygen therapy did not improve wound healing in these patients and that it dramatically increased treatment costs. 23,24 What is evident from our data is that these patients are at higher risk of complications and that they should be followed closely during the postoperative period.…”
Section: Discussionmentioning
confidence: 76%
“…[20][21][22] Our group and others, however, have demonstrated that hyperbaric oxygen therapy did not improve wound healing in these patients and that it dramatically increased treatment costs. 23,24 What is evident from our data is that these patients are at higher risk of complications and that they should be followed closely during the postoperative period.…”
Section: Discussionmentioning
confidence: 76%
“…Moreover, as the institutions involved in the current study gained more experience, it was recognized that the surgical resection and restoration of form and function in a complicated osteoradionecrosis setting was analogous to primary site composite resection and free flap reconstruction. 24,27 For many patients, the benefit of starting curativeintent therapy, without potential postoperative delays, may outweigh the potential risk of osteoradionecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, it seems clear that ORN surgery comes with a significant risk of complications (21% to 43%) and flap loss (0% to 14%) and thus should not be offered without restraint or until deemed absolutely necessary. 10,12 In fact, a growing body of literature now exists suggesting that flap loss rates are slightly higher in patients undergoing ORN reconstruction, with excellent resolution of disease when successful, when compared with other free tissue transfers (Table 1). 10,[12][13][14][15][16][17][18][19][20][21][22] This study was designed to identify factors contributing to postoperative morbidity to help counsel patients preoperatively regarding their individual risks of flap loss and surgical complications.…”
mentioning
confidence: 99%